Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper explores key features of Belgium's corporate income tax (CIT) regime as background for potential growth-enhancing reform options that also safeguard revenues and limit distortions. Comprehensive reform of business and investment income taxation in Belgium is both promising and challenging. The challenge arises from the need for fiscal consolidation and the limited scope for shifting the tax burden away from the CIT to other taxes. The absence of capital gains taxation undermines tax neutrality between different forms of businesses, leading to organizational inefficiencies and a misallocation of capital. Overall, there appears to be scope for a broader reform that could raise Belgium's growth potential without undermining fiscal revenues.